Penggunaan Media Kahoot! Sebagai Media Pembelajaran Maharah Kitabah (imla’) Bahasa Arab di Era Industri 4.0 - Nur Apriyanti Atika; Muassomah Muassomah (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2020)
Writing is one of the most recent language skills that must be mastered by learners. Writing in Arabic includes understanding how to write words consisting of a series of hijaiyyah letters. writing skills for grade 1 diniah are still often found in santri making mistakes in writing hamzah qotho and washol. Santri are still confused about the difference between hamzah washol and qotho ', and students are still mistaken which is hamzah washol and qotho'. If seen, Santri likes in the game.. In Pondok Nurul Huda Salafiah Safi'iyah is a salaf lodge where students allow to bring cellphones and laptops, this cottage is technology-based, and this cottage has provided wifi for internet nets so to overcome these problems, researchers use the application kahoot. The purpose of this study was to determine the benefits of kahoot media for students in writing skills lessons (Imla ') at Pondok Nurul Huda Salafiah Safi'iyah Malang, and to find out the concepts or steps of teachers using kahoot in writing skills lessons (Imla') in Pondok Nurul Huda Salafiah Safi'iyah Malang.